PENGABDIAN KEPADA MASYARAKAT PRODI TEKNIK MESIN PERTAHANAN AKMIL KEPADA MASYARAKAT KELURAHAN KARANGASEM KABUPATEN GUNUNG KIDUL YOGJAKARTA - Aryananta Lufti; Harjanto, Budi; Sukahar, Sukahar (PPM Sdirjianbang Akademi Militer, 2023)
Karangasem Village, which is located in the Gunung Kidul area, Yogyakarta, is a reflection of the long journey of the local community and its forerunners which are entwined in a rich history. The first trace in the history of Kelurahan Karangasem brings us back to the roots of the traditional culture that underlies people's lives in this region. The purpose of community service of the Defense Mechanical Engineering Study Program is as a manifestation of the implementation of the knowledge and skills possessed by Lecturers and Cadets to people's lives related to the field of mechanical engineering. The method used is direct practice in the field. The result of the community service was the achievement of socialization activities and free servicing of 35 motorbikes in the Karang Asem Village, Gunung Kidul, Yogyakarta.